2011
DOI: 10.5588/ijtld.10.0701
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and calcium levels in Ugandan adults with human immunodeficiency virus and tuberculosis

Abstract: SUMMARY BACKGROUND Vitamin D increases cathelicidin production, and might alter mortality due to tuberculosis (TB) in human immunodeficiency virus (HIV) co-infection. However, due to abundant sun exposure, vitamin D levels might be excellent among Ugandans with HIV and TB. METHODS We measured 25(OH)D and calcium levels in 50 HIV-negative, 50 HIV-infected and 50 TB-HIV co-infected Ugandan adults. RESULTS Mean ± standard deviation 25(OH)D levels were 26 ± 7 ng/ml in HIV-negative, 28 ± 11 ng/ml in HIV-infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 17 publications
(22 reference statements)
7
29
3
Order By: Relevance
“…1,2,4,5,11,12,14,23,28,30,3237,39,4043,46,47 Our analysis showed that VDD was significantly associated with an increased risk of TB (OR =2.57; 95% CI =[1.74, 3.80]; P <0.00001; I 2 =83) (Figure 2B). Subgroup analysis revealed similar result for the Asian population (OR =2.62; 95% CI =[1.63, 4.23]; P <0.0001; I 2 =71); however, VDD was not associated with an increased risk of TB in the African population (OR =1.89; 95% CI =[0.82, 4.33]; P =0.13; I 2 =91) (Figure 2B).…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…1,2,4,5,11,12,14,23,28,30,3237,39,4043,46,47 Our analysis showed that VDD was significantly associated with an increased risk of TB (OR =2.57; 95% CI =[1.74, 3.80]; P <0.00001; I 2 =83) (Figure 2B). Subgroup analysis revealed similar result for the Asian population (OR =2.62; 95% CI =[1.63, 4.23]; P <0.0001; I 2 =71); however, VDD was not associated with an increased risk of TB in the African population (OR =1.89; 95% CI =[0.82, 4.33]; P =0.13; I 2 =91) (Figure 2B).…”
Section: Resultsmentioning
confidence: 71%
“…1,4,5,11,12,14,22–28,30,3544,46 Our analysis with a random-effect model showed a significantly lower serum/plasma 25(OH)D level in TB patients vs controls (MD =−13.05; 95% CI=[−19.02, −7.08]; P <0.0001; I 2 =96) (Figure 2A). Subgroup analysis showed similar result for the Asian population (MD =−14.64; 95% CI =[−20.15, −9.13]; P <0.00001; I 2 =89); however, there was no such significant difference for the African population (MD =−6.05; 95% CI =[−20.54, −8.43]; P =0.41; I 2 =98) (Figure 2A).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…It has been proposed that vitamin D deficiency may predispose to TB-IRIS [67] and this would then place those at higher latitudes at greater risk of TB-IRIS. However, studies to date have not confirmed an association between baseline vitamin D status and IRIS risk [68,69].…”
Section: Discussionmentioning
confidence: 96%